Morphological Distinction and Phenotypic Variance of Mystus (Mystus gulio, M. nigriceps, and M. singaringan) from Java Island, Indonesia: Morphological analysis of three Javanese Mystus (Mystus gulio, M. nigriceps, and M. singaringan) - Ni Putu Anggun Larasati; Elok Amalia; Bintang Rhafsyanjani; Muhammad Dailami; Abd Rahem Faqih; Ating Yuniarti; Wahyu Endra Kusuma (Universitas Negeri Surabaya, 2026)
Genus Mystus is widely distributed across Indonesia with eleven currently valid species. Three species are confirmed to inhabit Java Island: Mystus gulio, M. nigriceps, and M. singaringan. Due to their similar morphological appearances and relatively subtle diagnostic features, species identification and discrimination between these three species is somewhat challenging. This study evaluates the morphological differentiation of M. gulio, M. nigriceps, and M. singaringan at both interspecific and intraspecific levels using samples collected across Java Island. Morphological data including thirty morphometric and five meristic characters from 143 individuals in sampling sites were analyzed using Principal Component Analysis (PCA) and UPGMA clustering. PCA (75.32% total variance) effectively discriminated the three species, identifying maxillary barbel length and adipose-fin base length as the primary diagnostic characters. Intraspecific analyses revealed high morphological homogeneity across geographic sampling sites; however, significant phenotypic variance was observed, primarily attributed to ontogenetic allometric growth in juveniles and localized environmental plasticity. Despite testing for novel morphometric and meristic markers, this study reinforces the reliability of traditional adipose and barbel proportions as the definitive tools for field identification. These results provide a critical morphological baseline essential for the conservation, germplasm verification, and potential domestication of these indigenous aquatic resources. Highlighted Finding 1. Maxillary barbels and adipose fins are key diagnostic traits for Javanese Mystus2. PCA results reveal a unique morphological divergence in the Bogor M. singaringan3. Findings prioritize M. singaringan for farming and M. nigriceps for conservation Graphical View